Seatbelt Use and Traumatic Brain Injury in Taiwan: A 16-Year Study - Chia-Ying Kuo; Hung-Yi Chiou; Jia-Wei Lin; Shin-Han Tsai; Yung-Hsiao Chiang; Chien-Min Lin; Wen-Ta Chiu (Tehran University of Medical Sciences, 2015)
Background: A motor vehicle seat belt use law for the driver and front-seat passenger was implemented in Taiwan on June 1, 2001. The purpose of this study was to determine the effect of motor vehicle seat belt use on the severity of traumatic brain injuries because of motor vehicle accidents. Methods: Data were collected from 27 major teaching hospitals four years before June 1, 2001 and until May 31, 2013. A total of 822 brain-injured patients with a mean age of 37.4 (± 13.4) years were included; 251 were injured prior to implementation of the law and 571 after. The Glasgow coma scale was adapted to rate the severity of traumatic brain injury on admission. The Glasgow outcome scale was used to categorize the outcome on discharge. Results: After the seat belt law was implemented, traumatic brain injuries were less severe (P<0.001) and the rates of loss of consciousness, neurologic deficit, intracranial hematoma, craniotomy, and poor physical condition at discharge were all significantly lower (all P< 0.05). Male gender, longer hospital stays, not wearing a seat belt, and injury before the law was enacted were all associated with poorer physical condition at the time of discharge (all P <0.01). Conclusion: Among occupants who survived a motor vehicle accident but had traumatic brain injuries, those who had worn seat belts had a better prognosis. Seat belts remain one of the best methods to reduce both the severity of injuries and the number of fatalities.